2001
DOI: 10.1046/j.0022-202x.2001.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Dendritic Cells as Targets of Dengue Virus Infection

Abstract: Dengue virus infections are an emerging global threat. Severe dengue infection is manifested as dengue hemorrhagic fever and dengue shock syndrome, both of which can be fatal complications. Factors predisposing to complicated disease and pathogenesis of severe infections are discussed. Using immunohistochemistry, immunofluorescence, flow cytometry, and ELISA techniques, we studied the cellular targets of dengue virus infection, at both the clinical (in vivo) and the laboratory (in vitro) level. Resident skin d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(142 citation statements)
references
References 21 publications
1
138
0
3
Order By: Relevance
“…Both CD209L and DC-SIGN mediate attachment of Sindbis glycoprotein via their CRDs and mediate productive infection by Sindbis virus, especially by virus produced in insect cells that has high levels of high mannose glycans on the envelope glycoproteins compared with virus produced in mammalian cells (30). DC-SIGN also mediates productive infection of human dendritic cells by dengue virus (31,32). DC-SIGN and CD209L glycoproteins bind hepatitis C virus glycoproteins E1 and E2 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Both CD209L and DC-SIGN mediate attachment of Sindbis glycoprotein via their CRDs and mediate productive infection by Sindbis virus, especially by virus produced in insect cells that has high levels of high mannose glycans on the envelope glycoproteins compared with virus produced in mammalian cells (30). DC-SIGN also mediates productive infection of human dendritic cells by dengue virus (31,32). DC-SIGN and CD209L glycoproteins bind hepatitis C virus glycoproteins E1 and E2 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that dendritic cells (DCs) are more permissive to DV infection compared with monocytes and macrophages (3,4). DC-specific ICAM-3-grabbing nonintegrin (DC-SIGN), a cell surface C-type lectin expressed on DCs, plays a critical role in DV binding and infection (5,6).…”
Section: Engue Viruses (Dv)mentioning
confidence: 99%
“…Recently, our group demonstrated that the presence of a mutation affecting the DV1-NS3 hel protein (L435S or L480S) correlates with increased viral replicative capacity both in vitro and in vivo by increasing RNA synthesis and the viral load, as well as by enhancing the inflammatory profile and mouse mortality [34]. In the present study, we sought to investigate how the same DV1-NS3 hel -mutated strains (vBAC-NS3 435 or vBAC-NS3 480 ) could modulate response of the primary targets of DV infection, human mdDCs [47]. Dendritic cells play a key role as an innate immune cell, triggering adaptive immune responses [23,24,45].…”
Section: Discussionmentioning
confidence: 99%